CONTAMINATION OF SOIL-TRANSMITTED HELMINTH (STH) EGGS ON FLY VECTORS AT THE SUKAWINATAN FINAL DISPOSAL SITE (TPA) IN PALEMBANG CITY - Fadhlu Ridho, Muhammad; Dalilah, Dalilah; Handayani, Dwi; Dwi Prasasty, Gita; Susilawati (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
In Indonesia, the prevalence of soil-transmitted helminths (STH) infection ranges from 2.5% to 62%, primarily affecting lower socioeconomic groups with poor sanitation. STH transmission can occur through fecal-oral routes, skin penetration of larvae, and mechanical vectors. This study examines STH egg contamination in flies at the Sukawinatan Landfill, Palembang, to understand their role in transmission and support vector control strategies. The research employs a descriptive observational study with a cross-sectional design. Observations were conducted microscopically with sample processed using the sedimentation technique. From 59 samples prepared from 598 flies, 17 samples (28.8%) were confirmed positive for STH eggs. The total number and type of STH eggs found were 24 Trichuris trichiura eggs. In conclusion, STH egg contamination was detected on flies at the Sukawinatan Landfill in Palembang City.